I am not Scared - Lalita Iyer (Bharat Om Books International, 2019)
Maya just failed her test in class. She knew Mama would be furious. She tried to hide things but that didn$1 (Bt help.Would deciding not to be scared really help? Find out as you read through the pages$1! =s
Keywords: Character And Competence ( Fiction ) -- Character And Competence ( Fiction )